General Anaesthesia in a patient with Danon Disease. Issue 2 (28th November 2013) - Schunke, Nicola; Green, David; Griffiths, Richard
Summary: Danon disease is a rare inherited disorder of glycogen storage. We describe the peri‐operative anaesthetic management of a 33 year old male with Danon disease for elective colorectal surgery in a district general hospital. There is a paucity of information in the anaesthetic literature related to the management of these patients, and we believe that this description will be of educational value to others faced with the challenge of anaesthetising these patients who have a high cardiovascular risk secondary to this rare genetic disorder.